Human neutrophil antigen allele frequencies and assessment of HNA alloimmunisation risk in donors and hematological patients - I. I. Krobinets; N. V. Mineeva; I. O. Bogdanova; A. V. Chechetkin (Бюллетень сибирской медицины, 2020)
Relevance. Human neutrophil antigens (HNAs) are localized on glycoproteins which are positioned on the surface membrane of human neutrophils. Alloantibodies against HNA are implicated in a number of clinical conditions, including immune-mediated neutropenia and transfusion reactions. Genotyping for HNA systems is important in the diagnosis of disorders involving alloimmunization to HNA.Aim. To assess the risk of HNA alloimmunization in donors and patients with hematological diseases in St. Petersburg based on the study of HNA allele and genotype frequencies.Materials and methods. DNA samples of 303 blood donors and 302 hematological patients were obtained and typed for HNA-1, -3, -4, -5. Polymerase chain reactions with homemade sequence-specific primers were used for typing. Genomic DNA was isolated from whole blood by a multistage purification method using the CTAB reagent. The results were detected in real time using the EVAGreen intercalating dye. Pearson’s chi-squared test was used to compare the HNA genotype frequencies in donors, patients with hematological diseases and in other populations.Results. In the study, the frequency of HNA-1bd allele was 0.584–0.588, of HNA-1a – 0.376–0.384, of HNA- 1bc – 0.032–0.036. HNA-1bc allele was represented in the genotypes HNA-1a/bc/bd (0.023–0.036), HNA-1a/bc (0.020–0.043) and HNA-1bc/bd (0.007–0.010). The genotypes HNA-1bc/bc and HNA-1null were not identified. Allele “a” of HNA-3, -4, -5 systems was found in the majority of studied individuals (0.795–0.804; 0.887–0.898; 0.699–0.708). The highest calculated risk of HNA alloimmunization was noted in the absence of HNA-5b, HNA- 1a, HNA-3b, and HNA-4b alleles in the genotype and was 0.250, 0.233, 0.231, and 0.163, respectively.Conclusions. Our data are consistent with the results of studies on the HNA allele and genotype frequencies in populations of Europeans and are significantly different from those of East and Southeast Asia, Africa and South America. The frequencies of HNA-1, -3, -4, -5 alleles and genotypes among donors in St. Petersburg and patients with hematological diseases did not have statistically significant differences. It was shown that the highest calculated risk of alloimmunization was observed in the absence of HNA-5b, HNA-1a, HNA-3b, and HNA-4b alleles in the genotype. These data are consistent with the results of similar studies on populations of white Europeans conducted by other authors.